Making a desired name: identity narratives in young university students who have committed transgressive offences - Amariles Villegas, Wilson Andrés; Bahamonde Olaya, Santiago (Revista Colombiana de Ciencias Sociales, 2024)
In Colombia, juvenile crimes constitute one of the most significant groups in penitentiary institutions. This phenomenon tends to be justified by poverty, inequality, lack of access to education, domestic violence, among others. However, these acts are not only linked to these sociodemographic characteristics, but they also involve family, relational, and subjective issues. The main purpose of this research was to identify how identity narratives are shaped in young people from private universities who have committed transgressive offences. To this end, research was carried out with a qualitative methodological approach, employing the narrative method through life stories. The narrative conversational interview was implemented with three young students from private universities who committed offences. For the analysis, the narrative method was applied using transcriptions and encodings of meaning units of the stories. Among the most significant results, there is the adolescent’s search for a desired status, not imposed, through transgression. Blunt events or acts as hinge moments in the identity generated by the transgression and a post-transgression identity permeated to the present by said event.